A narrative review of the psychological condition of a juvenile inmates - Fikri, Miftahul (Universitas Negeri Padang, 2019)
Data from the Indonesian Child Protection Commission said, from 2011 to the end of 2018, there were 11,116 children in Indonesia involved in criminal cases, various criminal cases committed by adolescents namely theft, drugs, abuse, immorality, and murder. The purpose of this study is to encompass epidemiological literature about the prevalence, risk factors, and psychological conditions of adolescents who commit crimes. The method used is a systematic process used to find literature about the causes of juvenile crime. The literature on these topics is summarized to provide an overview of these problems. The results found that too many teenagers which grow up in unhealthy circumstances, they are faced with many life challenges such as family, economy, and education that contribute to criminal behavior. It is hoped that this literature review will help community institutions, parents, and schools (school personnel: teachers, counselors) to improve arrangements for creating protection to minimize criminal cases in adolescents.Â